Integration and service composition based on model - Dyvak, Yu.; Mamedov, T. (PROBLEMS IN PROGRAMMING, 2022)
In the paper we would like to introduce a frame- work for designing and developing Semantic Web Service application that integrates a several enterprises and composes results from a diﬀerent services by applying techniques, methodologies and notations provided by Software Engineering and Business process modeling. We propose to use existing business modeling techniques (BPMN, BPLWS, OWL-S, WSDL, WebML) for modeling the cross enterprise processes, for enterprise integrations and web service compositions. The main purpose is to designing and developing semantically rich Web applications, with semiautomatic defining semantic descriptions from the business process model that increase the eﬃciency of design and decrease the extra work necessary for processing semantically annotated information which passing through the enterprises.Problems in programming 2022; 2: 37-46